Edukasi sebagai Upaya Peningkatan Kesehatan Anak Usia Dini - Nur Intan Kusuma; Eka Budiarto; Nur Chabibah; Rita Rahayu (Lembaga Pengembangan Kinerja Dosen, 2023)
Early childhood in children is an extraordinary stage of development. Children experience complex physical growth and mental development. The child's reaction and adaptation to environmental stimuli occurs quickly. However, at this time it is also prone to health problems including problems with malnutrition, stunting, obesity problems, respiratory and digestive tract infections, delays in speech development, and emotional problems. Therefore, education for parents to optimize early childhood health is urgently needed. This community service program aims to increase parental knowledge in improving early childhood health. This program was implemented in January 2023 with 25 parents attending the meeting. The method used in this activity is to provide education to parents by carrying out pre-test and post-test. The target of community service is all parents (mothers) who have early childhood children. Mothers have an average age of 32.72 years with an age variation of 4.89, the minimum age is 26 years and the oldest is 42 years. Most of them are housewives (68%) with the most education being high school or vocational school graduates, namely 40%. Providing education about optimizing early childhood health resulted in an average increase in mother's knowledge of 0.76 or the equivalent of 5.06%. These results indicate an increase in parental knowledge in improving early childhood health. This is expected to increase the capacity of parents in optimizing their child health.